Selected socio-economic factors of health literacy of the poor - Řimnáčová, Zuzana; Kajanová, Alena; Břízová, Bohdana (Walter de Gruyter GmbH, 2018)
Our article is focused on selected socio-economic aspects of health literacy of poor persons in the South Bohemian Region. In addition to determining the level of health literacy, we test its relationship to income and education level and examine how difficult it is for the target group to pay for medicines and visit a physician if needed. We also focus on the causes of such difficulties. The research was conducted in 2016 on a sample of 254 persons entitled to state material poverty benefits in the South Bohemian Region. A structured interview was used, including the administration of the short form of the standardized Health Literacy questionnaire, with several additional questions on the respondents’ socio-economic situation. The data were statistically processed using SPSS. The results showed the respondents had an insufficient level of health literacy, and that a high proportion had difficulty paying for medicines and visiting their physician when required. Health literacy is not related to income but to education level.
Vybrané socioekonomické faktory zdravotní gramotnosti chudých
Keywords: health literacy; poor people; socio-economic factors; zdravotní gramotnost; chudí; socioekonomické faktory